Post-irradiation vertebral and carotid stenosis heightens stroke risk in head and neck cancer - Jian-Lin Jiang; Joseph Tung-Chieh Chang; Bing-Shen Huang; Ting-Yu Chang; Pi-Shan Sung; Yi-Chia Wei; Chien-Yu Lin; Chih-Hua Yeh; Kang-Hsing Fan; Chi-Hung Liu (BMC Cancer)
Abstract Background The relative risk of ischemic stroke (IS) in head and neck cancer (HNC) patients developing carotid artery stenosis (CAS) or vertebral artery stenosis (VAS) after radiation therapy (RT) remains uncertain due to limited studies, complicating vascular follow-ups and preventive strategies. Methods We included HNC patients who received RT between 2010 and 2023. The patients were divided into nasopharyngeal carcinoma (NPC) and non-NPC groups. The primary outcome was the occurrence of IS after RT, and the secondary outcomes included the development of > 50% CAS or > 50% VAS after RT. Results Of the 1,423 HNC patients, there were 19% of patients developed > 50% CAS, 6.8% of patients developed > 50% VAS, and 2.3% of patients developed IS. In patients with HNC, > 50% CAS (adjusted hazard ratio [HR] = 3.21, 95% confidence interval [CI] = 1.53–6.71), and > 50% VAS (adjusted HR = 2.89, 95% CI = 1.28–6.53) were both the independent predictors of IS. In the patients with NPC, > 50% CAS was an independent predictor of anterior circulation IS (adjusted HR = 4.39, 95% CI = 1.17–16.47). By contrast, > 50% VAS emerged as a predictor of posterior circulation IS in both the NPC (adjusted HR = 15.02, 95% CI = 3.76–60.06) and non-NPC groups (adjusted HR = 13.59, 95% CI = 2.21–83.46). Conclusion HNC patients with > 50% CAS or > 50% VAS after RT had an increased risk of IS within their corresponding vascular territory. CAS could be an important predictor of IS in NPC patients, whereas VAS might also be a significant predictor of IS in both NPC and non-NPC patients. Evaluation both the carotid and vertebral arteries after RT might be necessary. Trial registration ClinicalTrials.gov identifier No.: NCT06111430.